2011
DOI: 10.1111/j.1751-7915.2011.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and physiological properties of bacteriophages from North America and Germany affecting the fire blight pathogen Erwinia amylovora

Abstract: SummaryFor possible control of fire blight affecting apple and pear trees, we characterized Erwinia amylovora phages from North America and Germany. The genome size determined by electron microscopy (EM) was confirmed by sequence data and major coat proteins were identified from gel bands by mass spectroscopy. By their morphology from EM data, φEa1h and φEa100 were assigned to the Podoviridae and φEa104 and φEa116 to the Myoviridae. Host ranges were essentially confined to E. amylovora, strains of the species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…The streptomycin‐resistant EPS‐negative mutant of Er. amylovora CFBP1430 carries a Tn5 insertion in amsD (Müller et al ., ,). Escherichia coli strain XL1‐Blue MRF' (Agilent Technologies, Santa Clara, CA, USA) was cultivated in LB at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The streptomycin‐resistant EPS‐negative mutant of Er. amylovora CFBP1430 carries a Tn5 insertion in amsD (Müller et al ., ,). Escherichia coli strain XL1‐Blue MRF' (Agilent Technologies, Santa Clara, CA, USA) was cultivated in LB at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Bacteriophages specific for Er. amylovora were first reported several decades ago (Erskine, 1973), and more recently followed by studies regarding their characterization and application to control the pathogen (Schnabel and Jones, 2001;Gill et al, 2003;Born et al, 2011;Boulé et al, 2011;Müller et al, 2011b;Schwarczinger et al, 2011;Nagy et al, 2012). Clearly, the extreme specificity of phages to kill only their host bacteria without affecting other members of the bacterial ecosystem offers significant potential for environmentally friendly pathogen control.…”
Section: Introductionmentioning
confidence: 99%
“…2 Biocontrol of bacterial plant pathogens using bacteriophages (phages) has gained increased attention in agriculture as an alternative treatment, 3,4 and several studies have demonstrated the potential of phages to control fire blight. Phage-treatment significantly reduced the number of viable E. amylovora and symptom development in vitro, 5,6 on immature pear fruit, 7,8 on detached flowers, 8,9 and on apple trees. 9,10 Furthermore, "Erwiphage", a bacteriophage cocktail consisting of two phages, was recently introduced and is commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriophages (phages) offer a novel biological control mechanism since they are ubiquitous in the orchard environment, self‐replicating, nontoxic to eukaryotes, biodegradable unlike many agrochemicals and usually species and strain specific with no effect on indigenous bacteria. Phage‐mediated control of fire blight has been studied in laboratory and under field conditions (Erskine, ; Gill et al ., ; Lehman, ; Müller et al ., ; Svircev et al ., 2010; 2011; Boulé et al ., ; Schwarczinger et al ., ; Nagy et al ., ). Erskine () first demonstrated that a temperate phage that lysogenized a yellow saprophytic bacterium reduced fire blight symptoms when co‐inoculated with E. amylovora on pear slices.…”
Section: Introductionmentioning
confidence: 99%